ANTIOXIDANT ACTIVITY in vitro OF AQUEOUS EXTRACT OF Allium sativum variety HUARALINO - Suárez Cunza, Silvia (2014)
The aim of this studio was to evaluate in vitro the bulb antioxidant activity of Allium sativum var. huaralino. Tests were conducted to study the sulfur secondary metabolites, allicin and quantifying organic compounds of low molecular weight with thiol group. For oxygenated metabolites it was evaluated polyphenols and flavonoids. These assays were performed by spectrophotometry. Mineral was also quantified by atomic absorption. Assays for in vitro antioxidant activity were made ?by carbonyl formation in albumin treated with hydrogen peroxide and thiobarbituric acid reactive species (TBARS) levels in red blood cells also treated with hydrogen peroxide. The main results of sulfur and oxygenated metabolites were: a) allicin 2.8 mg / g of fresh peeled bulb, b) low molecular weight thiols µmol 0.95 cysteine (Cys)/g dry mass, c) 2.52 mg polyphenols EAG / g dry mass d) EQ 1.71 mg / g dry mass. The extract had antioxidant protection: decreased significantly the formation of protein carbonyl and TBARS levels (p <0.05). In conclusion, the aqueous extract of Allium sativum var. huaralino bulb has oxygenated and sulfur antioxidant metabolites capable of exerting an antioxidant effect in vitro.